PENGARUH KEBIASAAN MAKAN MAKANAN PEDAS TERHADAP KEJADIAN SINDROM DISPEPSIA FUNGSIONAL DI POLIKLINIK PENYAKIT DALAM RUMAH SAKIT UMUM HAJI MEDAN - PUTRI KIRANI; PINTA PUDIYANTI SIREGAR (LP2MTBM MAKARIOZ, 2022)
Dyspepsia syndrome is a health problem that is very often encountered in daily life, health complaints related to eating or complaints related to gastrointestinal disorders. There are several risk factors that cause dyspepsia syndrome, one of which is diet or eating patterns. Someone who has a habit of eating spicy food can increase the risk of functional dyspepsia syndrome. The object of research are to determine the effect of eating spicy food on the incidence of functional dyspepsia syndrome in the internal medicine polyclinic of Haji General Hospital Medan. The research method used a descriptive analytic design with a cross sectional method. The sample in this study amounted to 64 people using purposive sampling technique. Data collection was obtained from primary data by taking anamnesis and filling out questionnaires for patients at the internal medicine clinic at Haji Medan General Hospital. The reselt are of univariate analysis showed that the highest number of respondents based on age was in the early adult category (26-35 years) (48.4%), based on gender the most were women (67.2%). In this study, there were 38 people who were positive for functional dyspepsia syndrome and 25 of them had a habit of frequently consuming spicy food. Based on the results of the Chi-Square test, there was a significant relationship between the habit of consuming spicy food and the incidence of functional dyspepsia syndrome (p = 0.001). the conclusion of this research is a significant relationship between the habit of consuming spicy food with the incidence of functional dyspepsia syndrome